2014
DOI: 10.5194/os-10-759-2014
|View full text |Cite
|
Sign up to set email alerts
|

Variability of water mass properties in the Strait of Sicily in summer period of 1998–2013

Abstract: Abstract. The Strait of Sicily plays a crucial role in determining the water-mass exchanges and related properties between the western and eastern Mediterranean. Hydrographic measurements carried out from 1998 to 2013 allowed the identification of the main water masses present in the Strait of Sicily: a surface layer composed of Atlantic water (AW) flowing eastward, intermediate and deep layers mainly composed of Levantine intermediate water (LIW), and transitional eastern Mediterranean deep water (tEMDW) flow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 34 publications
5
45
1
Order By: Relevance
“…The S signal was less intense, visible mainly in 1991–1993, prior to the start of the mooring record 14 . The successively observed S increase, up to mid-2000, is consistent with previous studies 14, 16, 17 .…”
Section: Resultssupporting
confidence: 92%
“…The S signal was less intense, visible mainly in 1991–1993, prior to the start of the mooring record 14 . The successively observed S increase, up to mid-2000, is consistent with previous studies 14, 16, 17 .…”
Section: Resultssupporting
confidence: 92%
“…In addition, the spatial extension of AIS path may have had important consequences on the predominant hydrological phenomena occurring in the region, such as the offshore extension of coastal upwelling . In summer 2009, the flow of the stream moved further offshore (Bonanno et al, 2014) and so the study area showed a broader upwelling extension centred…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In particular, an increase in nutrient concentration in deeper layers of the euphotic zone, together with a strengthened stratification of the water column, due to the increase in the surface water temperature, has been observed in the Mediterranean Sea [1,14,88,89]. Here, at the same time, global climate change has also triggered more frequent and severe tropical …”
Section: Discussionmentioning
confidence: 96%